Fragmented palmar metacarpophalangeal sesamoids in dogs: a long-term evaluation - Mathews, K. G.; Koblik, P. D.; Whitehair, J. G.; Kass, P. H.; Bradley, C. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Long-term clinical and radiographicresponse to surgical and conservativemanagement of 22 dogs with fragmentedsesamoids was evaluated. Mean follow-up was 3.6 years (range = 3 monthsto 11.0 years).Initial (retrospective) and follow-up(prospective) radiographs of the affectedpalmar sesamoids and associatedmetacarpophalangeal joints were evaluatedusing a graded scoring system. A lameness evaluation and physicalexamination were performed at followupin a blinded manner. In addition,owners were asked to complete a questionnaireregarding their pet’s thoraciclimb lameness.There was not any difference betweengroups (sesamoidectomy, conservativemanagement, incidental finding)in age at onset, duration of lamenessprior to therapy, body weight at treatment, time to follow-up, number ofaffected joints, nor owner perceptionsof whether they thought the lamenessimproved, resolved, or recurred, andwhether or not they were pleased withthe outcome.Sesamoid fragmentation treated bysesamoidectomy resulted in significantlygreater progression of radiographicchanges that were consistentwith degenerative joint disease.Chronic lameness resolved or improvedto the point of owner satisfactionwith conservative therapy in most cases. Continued lameness, or recurrent,although improved lameness associatedwith heavy activity, occurred followingsurgical extirpation of the affectedsesamoids in many cases. Given thesefindings, a more conservative approachto the treatment of chronic lamenessassociated with sesamoid fragmentationmay be warranted.Long-term clinical and radiographic response to surgical and conservative management of 22 dogs with fragmented sesamoids was evaluated. Mean follow-up was 3.6 years. Sesamoid fragmentation treated by sesamoidectomy resulted in significantly greater progression of radiographic changes that were consistent with degenerative joint disease. Chronic lameness resolved or improved to the point of owner satisfaction with conservative therapy in most cases. Continued or recurrent lameness was common following sesamoidectomy. Conservative therapy should be attempted prior to sesamoidectomy for dogs with chronic lameness associated with palmar metacarpophalangeal sesamoid fragmentation.
Keywords: Metacarpophalangeal; sesamoid; sesamoidectomy; conservative management